Karelian Female Names - Denis V. Kuzmin (Вопросы Ономастики, 2017)
The article analyzes the system of personal female names of the Karelian population. As the author demonstrates, the collected corpus of historical and modern Karelian women’s names is yet very incomplete and severely understudied. This may be due to a number of factors, including the relative scarcity of female names recorded in historical documents and in toponymy, the limited number of sources, the lack of fundamental Russian-based research and dictionaries devoted to female names, which were often a source for many historical Karelian forms. For this reason, first, a significant part of the article deals with the reconstruction of the pre-Christian corpus of Karelian female names, as reconstructed from folklore texts and animal. The author pays special attention to the latter type of data, which was hardly considered in previous anthroponymic research. In his view, after the Christianization of the Karelians, the pagan system of names was not entirely lost, but relegated to a lower “domestic” sphere, including naming of cows and other animals. And second, based on historical documents and toponymy, the article gives a close examination of Christian female names and their numerous folk forms, which became widespread after the Christianization of the Karelians in 1227. By giving multiple evidence of such names and their forms, the author investigates the patterns of phonetic and morphological adaptation of the Russian versions of female names in the Karelian language. The study covers the data from all major settlement territories of the Karelians (Republic of Karelia, Finland, Leningrad, and Tver regions of Russia).